MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI MODEL PEMBELAJARAN PROBLEM POSING PADA MAHASISWA PENDIDIKAN MATEMATIKA - Lizza Novianita; Saleh Haji (Universitas Muhammadiyah Bengkulu, 2020)
The purpose of this research is to improve mathematical communication skills through the Problem Posing learning model. The method used in this research is (Classroom Action Research). The subjects of the study were 11 students of Mathematics Education Study Program FKIP Bengkulu University 11 students in conference courses in odd semester 2019/2020. Stages of Study for Classroom Action are planning, implementing, observing, and reflecting. The results obtained after being given an action is an increase in student communication skills through the Problem Posing learning model compared to learning before that increase by 60.Keywords: Communication Ability, Problem Posing